Penerapan Etika Bisnis Islam Pada Café Dedy Di Trans Pir Unit 3 Dalam Perspektif Ekonomi Islam - Ulfah Masruroh; H. Junda Harahap; Enni Efrida Nasution (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
Based on the results of the research conducted that (1) the application of business ethics from an Islamic economic perspective, namely maintaining Muslim entrepreneurial behavior such as the ethics carried out by the Prophet Muhammad in business, namely the characteristics of shiddiq, amanah, fathanah, tabligh, because in Islam there are also ethical rules that must be followed by business people and businesses. Alone. (2) The application of business ethics at Café Dedy is largely in accordance with Islamic business ethics. Islamic ethics includes the nature of shiddiq, which is demonstrated by not doubling the price of goods, being honest in measurements, and ensuring that the products sold do not include items prohibited in Islam. The characteristics Tabligh Café Dedy implements include communicating in a friendly manner, having a vision and mission that does not conflict with Islamic law, and establishing friendship with consumers. Trustworthiness also means keeping promises and providing reports to the owner regarding the money received and expenses made, which is a characteristic of hard working people. The nature of fathanah reflects the spiritual state of owners and employees who do not forget to worship Allah. Some of Dedy's cafes are not yet in accordance with Islamic business ethics, namely in terms of keeping promises; keeping promises to consumers in terms of ordering time, which is promised to be a maximum of 25 minutes, but sometimes it can be longer due to various factors such as kitchen factors and employees who work slowly and also employees' less careful attitude in checking delivery orders so that orders can be made wrong.